Determination of the Keyhole Position in a Lateral Suboccipital Retrosigmoid Approach - TERANISHI, Yu (Neurol Med Chir (Tokyo), 2014)
Appropriate placement of the keyhole at the transverse and sigmoid sinus (T/S) junction is important for performance of safe and accurate lateral suboccipital craniotomy with minimum bone loss. Here, we report a method for predicting the position of the T/S junction and investigate the relationship between the T/S junction and asterion. The subjects were 88 patients treated surgically via a lateral suboccipital approach. These cases included 78 acoustic neuromas, 4 meningiomas, 1 trigeminal schwannoma, 1 epidermoid cyst, 2 trigeminal neuralgias, and 1 hemifacial spasm. To expose the T/S junction, we usually place the keyhole lateral to asterion by a half diameter of the burr hole. The distance of the T/S junction from asterion was investigated using three-dimensional computed tomography (3DCT) images. We investigated the differences between the actual and predicted positions of the T/S junction based on skull landmarks, and we compared our method with other literature methods. The mean distances were 5.7 mm caudal and 6.6 mm lateral. The difference between the actual and predicted positions was significantly smaller in our approach compared to other methods. Placing the keyhole lateral to a provisional burr hole just caudal to asterion and lateral by half the diameter of the burr hole was useful for exposure of the T/S junction. The best approach is to use preoperative 3DCT, but this may be limited by equipment problems, emergency cases, or allergy to contrast medium. Determination of the appropriate keyhole position with reference to skull landmarks is a universally useful method.